A 87.5-dB-SNDR Residue-integrated SAR ADC with a Digital-domain Capacitor Mismatch Calibration - Ku, Hwan-Seok; Choi, Seungnam; Sim, Jae-Yoon (Journal of semiconductor technology and science, 2021)
This paper presents an asynchronous-clocking 16-bit successive approximation register (SAR) analog-to-digital converter (ADC) suitable for high-precision sensor applications. Comparator noise and nonlinearity from capacitor mismatch, as two major performance-limiting problems of SAR ADC, are resolved by noise averaging with a residue integration and a digital-domain capacitor error calibration, respectively. The proposed ADC is implemented using 180-nm CMOS technology in an area of 0.68mm2. The calibration improves SNDR by 5.9 dB and SFDR by 14.3 dB, achieving an SNDR of 87.5 dB and an SFDR of 106.85 dB, respectively. KCI Citation Count: 1